Education as the Management of Research Universities Students’ Socialization - Petrova, Tatyana N.; Kirillova, Olga V.; Sokolova, Svetlana G.; Pugacheva, Natalya B.; Galimullina, Alfiya F.; Maksimova, Olga G.; Antonova, Tatyana V.; Kozhanov, Vladimir V. (International Review of Management and Marketing, 2016)
The relevance of the study is reasoned by the demand for professionals who are not only competitive in the labor market, but also ready to construct career in the flow of social transformations. The processes of socialization and vocational education are dialectically interrelated. Education, as a structural component of vocational education is considered as the management process of socialization, providing personal self-realization, its positioning as an active entity of social reality. The purpose of the paper is to identify the characteristics of education as a management process of research universities students’ socialization. The leading method is the method of action research (AR), allowing to obtain new knowledge about education as the management of socialization process and to propose methods of educating of research universities students. The article defines the essence of socialization, as a process of assimilation of social experience by joining the social environment and active reproduction of social relations’ system; functions are clarified (assimilation of social information, the development of diverse forms of activities and communication, the awareness of being the actor of social reality, self-realization, participation in the reproduction of social experience) and types (positive, negative, reformation) of socialization; the features of education as a students’ socialization process management are revealed (subjectivity, adaptability, humanity, dedication, nationality); the methods of education are proposed (psychological-pedagogical, subject-creative, cognitive-oriented) as the management process of research universities students’ socialization. Article Submissions can be useful for teachers of research universities; for centers of personnel advanced training and retraining in the training content selection and structuring of research universities’ scientific and pedagogical staff. Keywords: Research Universities, Self-Realization, Personal Significant Actions, Functions of Socialization. JEL Classifications: A23, I23, I26